Will the Gig Economy Prevail? - Colin Crouch (Journal of Economic Sociology, 2019)
The book Will the Gig Economy Prevail? by Prof. Colin Crouch is devoted to the “gig economy,” which is seen as set to gradually replace the costly rigidities of the old-fashioned employment contract. In this book, Colin Crouch takes a step back and questions this logic. He shows how the idea of an employee— a stable status that involves a bundle of rights—has maintained a curious persistence. Examining the ways companies are attacking these rights, from proffering temporary work to involuntary part-time work to “gigging,” he reveals the paradoxes of the situation and argues that it should not and cannot continue. He goes on to propose reforms to reverse the perverse incentives that reward irresponsible employers and punish good ones, setting out an agenda for a realistic future of secure work. The Journal of Economic Sociology publishes the first chapter—“The Rise of Precarious Work”—in which the author considers the notion of the “gig economy” and issues associated with its expansion. It also describes the structure of this book.